ANALYSIS OF THE INFLUENCE OF BRAND IMAGE, SERVICE QUALITY AND STORE ATMOSPHERE ON CUSTOMER SATISFACTION CAFE RUANG SARCA MEDAN - Euodia Grace Maranatha; Endang Sulistya Rini; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Based on data from the Ministry of Tourism and Creative Economy, in 2021, the creative industry will contribute quite a lot to the GDP of the national economy, up to 6.98 percent, almost 7 percent with a value of no less than Rp. 1.134 trillion (Ghofar, 2022). The Ministry of Tourism and Creative Economy explained that there are 17 sub-sectors of the creative economy in Indonesia, namely: game developer, architecture, interior design, music, fine arts, product design, fashion, culinary, (animated film and video photography), visual communication design, television and radio, craft, advertising, performing arts, publishing, and applications (Kemenparekraf, 2022), based on 17 (seventeen) sub-sectors of the creative economy in Indonesia, culinary is the largest contributor (30%) from the tourism and creative economy sectors. The culinary industry has a very strong potential for development, so that the culinary industry receives great attention from the government so that this sector can progress by providing facilitation such as business training, access to capital, and business start-up assistance. In addition, the Ministry of Tourism and Creative Economy also participates in promoting this very diverse Indonesian cuisine in domestic and foreign markets (Kemenparekraf, 2022).